Simple Holographic Patterning for High‐Aspect‐Ratio Three‐Dimensional Nanostructures with Large Coverage Area. (7th September 2012) - Wathuthanthri, Ishan; Liu, Yuyang; Du, Ke; Xu, Wei; Choi, Chang‐Hwan
Abstract Using the vertical standing wave phenomena commonly regarded as a deterrent in holographic lithography, multifaceted three‐dimensional (3D) nanostructures are fabricated on polymeric photoresist materials using a simple two‐beam interferometer. Large‐area 3D nanostructures with high aspect ratios (greater than 10) are readily produced using this methodology, including grating, pillar and pore patterns. Furthermore, manipulation of the lithography process conditions results in unique sidewall profiles of the nanostructures. Such 3D holographic control even produces highly porous polymer membranes composed of 3D interconnected pore networks, which resembles the 3D photonic crystal compound nanostructures that were previously attainable only with limited pattern coverage area using complex multibeam holographic lithography processes. Such well‐tailored high‐aspect‐ratio 3D nanostructures with large pattern coverage area further enable the fabrication of novel nanostructures for functionalized materials via various additive and subtractive pattern transfer techniques such as etching, deposition, and molding. In particular, direct molding followed by thermal decomposition process leads to the synthesis of hierarchical titanium oxide nanostructures of tunable 3D geometry, which would be of great significance in applications of photonic crystals, photovoltaic solar cells, and photocatalyst in water decontamination.